1967
DOI: 10.1139/b67-143
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Changes in Rate of Anticlinal Division, Cambial Cell Length, and Ring Width in the Growth of Coniferous Trees

Abstract: The early growth of a tree is marked by a widening of the annual increments, a deceleration in rate of multiplicative (anticlinal) division of fusiform cambial cells, and an increase in cell length. Distance outward from the pith at which maximation in cell size occurs, and subsequent trends in cell dimensions, are apparently modified by rate of growth. Continuation of a uniform ring width through the middle to late years favors comparative constancy in rate of anticlinal division and cell size during that sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

1974
1974
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 9 publications
2
25
0
1
Order By: Relevance
“…As in Siberia, the larch trees have been observed to grow slower (Karlman et al 2005;Koizumi et al 2003) than the studied larches (Luostarinen 2011), the difference in FL between Siberian grown trees and the planted trees used in this study was in accordance with the observations made regarding the relationship between growth rate and FL in several softwoods: in narrow annual rings, the fibres get longer than in wide annual rings (Herman et al 1998;Nekhaichuk and Bryantseva 1984; Use of larch as raw material for pulp and paper industry 1971; Utunen 2008). This correlation did not occur in the outermost studied wood; however, perhaps because cambium had reached an age in which senescence starts: senescence decreases the lengthening of cambial initials (Bannan 1967). The change in growth at approximately this age from the pith (ca.…”
Section: Discussionmentioning
confidence: 87%
“…As in Siberia, the larch trees have been observed to grow slower (Karlman et al 2005;Koizumi et al 2003) than the studied larches (Luostarinen 2011), the difference in FL between Siberian grown trees and the planted trees used in this study was in accordance with the observations made regarding the relationship between growth rate and FL in several softwoods: in narrow annual rings, the fibres get longer than in wide annual rings (Herman et al 1998;Nekhaichuk and Bryantseva 1984; Use of larch as raw material for pulp and paper industry 1971; Utunen 2008). This correlation did not occur in the outermost studied wood; however, perhaps because cambium had reached an age in which senescence starts: senescence decreases the lengthening of cambial initials (Bannan 1967). The change in growth at approximately this age from the pith (ca.…”
Section: Discussionmentioning
confidence: 87%
“…The relationship between site conditions, growth rate and wood properties has been inconsistent as reported in the literature. Many studies have found that higher growth rates (better environmental conditions) result in shorter fibre lengths [12,53,54]. Mansfield et al [51] found that site conditions had no significant effect on the initial age of increasing fibre length for lodgepole pine.…”
Section: Discussionmentioning
confidence: 99%
“…2 Mean characteristics as a function of ring number from pith to bark. a Diameter growth, b fiber length, c fiber diameter, d fiber wall thickness diamond 3 m 9 4 m without alfalfa, square 3 m 9 4 m with alfalfa, triangle 3 m 9 6.7 m with alfalfa, circle 3 m 9 8 m with alfalfa, multiplication sign 3 m 9 10 m with alfalfa rate of anticlinal division is accompanied by short cells (Bannan 1967), a negative effect of growth rate on fiber length was expected to be found. In practice however, a completely different result was found.…”
Section: Discussionmentioning
confidence: 99%